Dampak Penggunaan Pestisida Kimia Terhadap Kualitas Tanah dan Air Sungai di Daerah Pertanian - Ahmad Dhiyaul Dhaifulloh; Balqist Iqfirlana Khayumi; Deul Tirtayuda Legawa; Muhammad Karfin Ardy Ansya; Denny Oktavina Radianto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Background: Modern agriculture often relies on the use of pesticides to control pests and plant diseases. However, the use of this pesticide can have a negative impact on the environment, especially on the quality of soil and river water in agricultural areas. This research aims to investigate the impact of pesticide use on soil and river water quality, with a focus on the type of pesticide used, usage patterns, and its impact on the environment and human health. Method: The journal research method with the literature review method is an approach used to collect, broadcast and synthesize information from various relevant literature sources Results: The use of pesticides in agriculture has a significant impact on the environment and human health. Appropriate methods of using pesticides, such as the correct dose and application time, as well as sustainable agricultural approaches such as organic farming, can reduce the negative impacts of pesticides. Farmer education about the safe use of pesticides is also important. In addition, soil and water quality must be considered in agriculture to maintain soil fertility and air ecosystems. River protection and rehabilitation efforts are also needed to maintain good river water quality.